2022
DOI: 10.48550/arxiv.2204.12380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-task Learning for Concurrent Prediction of Thermal Comfort, Sensation, and Preference

Abstract: Zusammenfassung-Indoor thermal comfort immensely impacts the health and performance of occupants. Therefore, researchers and engineers have proposed numerous computational models to estimate thermal comfort (TC). Given the impetus toward energy efficiency, the current focus is on data-driven TC prediction solutions that leverage state-of-the-art machine learning (ML) algorithms. However, an indoor occupant's perception of indoor thermal comfort (TC) is subjective and multidimensional. Different aspects of TC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the course of our earlier field survey in India during the summer season [47,48], it was observed that numerous primary school students were sent home early after they complained about being unwell (due to overheating and the extreme heat in the classrooms). In Table 8, the percentage of students who returned home early from their school schedule because of feeling unwell due to heat, as reported by the current survey, is demonstrated.…”
Section: Teachers' Experiences Related To Children's Heat Riskmentioning
confidence: 99%
“…In the course of our earlier field survey in India during the summer season [47,48], it was observed that numerous primary school students were sent home early after they complained about being unwell (due to overheating and the extreme heat in the classrooms). In Table 8, the percentage of students who returned home early from their school schedule because of feeling unwell due to heat, as reported by the current survey, is demonstrated.…”
Section: Teachers' Experiences Related To Children's Heat Riskmentioning
confidence: 99%